Financial Feasibility Analysis of Rice Farming in Dawuan Barat Village, Cikampek Subdistrict, Karawang Regency - Aditia Muhamad Ilham; Mohamad Sam’un; I Putu Eka Wijaya (Journal of Social Research, 2026)
Rice farming plays an important role in supporting national food security and the rural economy in Indonesia. However, rice farmers face several challenges, including increasing production costs, limited farming capital, land conversion, and uncertainty in agricultural sustainability. Dawuan Barat Village, Cikampek District, Karawang Regency, is one of the rice production centers with high agricultural potential, but farmers still experience constraints related to land ownership, rental costs, and production inputs. This study aims to analyze the financial feasibility of rice farming in Dawuan Barat Village based on production costs, revenue, income, and feasibility indicators. The research used a quantitative descriptive method conducted in August 2023. Data were collected through observation, interviews, and questionnaires involving 35 selected farmers using a simple random sampling technique from a population of 131 farmers. The analysis employed cost, revenue, income, Revenue-Cost Ratio (R/C Ratio), and Break Even Point (BEP) calculations. The results showed that the average production cost was IDR 31,226,778 per planting season per farmer, with revenue of IDR 48,834,286 and income of IDR 17,607,508. The R/C Ratio value reached 1.56, indicating that rice farming is financially feasible. Furthermore, BEP analysis demonstrated that the selling price, production volume, and revenue exceeded the break-even point. Based on land-scale analysis, small, medium, and large-scale farmers also obtained R/C Ratio values above 1. Therefore, rice farming in Dawuan Barat Village is profitable and feasible to be continuously developed.